Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11242-017-0896-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flow Through Porous Media: Numerical Prediction of the Contribution of Slip to the Apparent Viscosity

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18221 Abstract The flow of polymer solutions in porous media is often described using Darcy's law with an apparent viscosity capturing the observed thinning or thickening effects. While the macroscale form is well accepted, the fundamentals of the pore-scale mechanisms, their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Thus, the fluid motion is excited over a broad range of spatial and temporal scales, similar to high‐Re turbulence; intriguingly, however, this power law decay (with a −3.5 exponent) has a different value than the −5/3 Kolmogorov exponent characteristic of high‐Re turbulence. Simulations are able to recover a similar spectral scaling, supporting the idea that it reflects an elastic instability analogous to turbulence; they also reveal that flow fluctuations are stronger near boundaries, potentially due to a depletion layer effect …”
Section: Unstable Flow Of Polymer Solutionssupporting
confidence: 59%
See 2 more Smart Citations
“…Thus, the fluid motion is excited over a broad range of spatial and temporal scales, similar to high‐Re turbulence; intriguingly, however, this power law decay (with a −3.5 exponent) has a different value than the −5/3 Kolmogorov exponent characteristic of high‐Re turbulence. Simulations are able to recover a similar spectral scaling, supporting the idea that it reflects an elastic instability analogous to turbulence; they also reveal that flow fluctuations are stronger near boundaries, potentially due to a depletion layer effect …”
Section: Unstable Flow Of Polymer Solutionssupporting
confidence: 59%
“…This depletion layer arises from a combination of shear‐induced migration, entropic or steric effects, and electrostatic interactions . Though typically neglected from macroscopic models of flow, the formation of a depletion layer could play a considerable role on transport—for example, possibly suppressing polymer adsorption and leading to viscosity reduction at the pore surfaces . Nanofluidic platforms, which provide a means to test pores of width approaching molecular dimensions, could shed light on these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the latter allow a gain in accuracy, the use of collocated grids easily aligns the computational points to the experimental datasets. Optimized grid-based methods may be coupled to other methods dedicated to the flow features to be investigated: transport based on particle methods [54,55], anisotropic diffusion for space-variable medium [56,57], phase-field description of multi-phase flows [58,59] and its upscaling [8,60], complex fluid and rheology [61,57], etc...…”
Section: A Numerical Methodsmentioning
confidence: 99%
“…Morais et al (2009) simulated the flow of shear thinning fluids in 3D disordered porous media with large porosity, and proposed a universal curve for describing the relation between the effective permeability and a suitably-defined Reynolds number. Flow of a ST fluid through an array of cylinders was studied by Zami-Pierre et al (2018), who reported that disorder reduces the effect of the nonlinearity on the average flow. Sahimi (1993) used the critical path analysis to derive an expression for the effective permeability of power law fluids, including ST ones, in a porous medium.…”
mentioning
confidence: 99%